SUBACUTE MYOCARDITIS: MYTHS AND REALITY - P. A. Shesternya; V. A. Shulman; K. V. Zlodeev; E. A. Suglobova; D. V. Yurin (Klinicist)
Clinical case of subacute myocarditis is presented, complexity of its diagnosis and management are considered.